A village in a dish model system for population-scale hiPSC studies - Drew R. Neavin; Angela M. Steinmann; Nona Farbehi; Han Sheng Chiu; Maciej S. Daniszewski; Himanshi Arora; Yasmin Bermudez; Cátia Moutinho; Chia-Ling Chan; Monique Bax; Mubarika Tyebally; Vikkitharan Gnanasambandapillai; et al. (Nature Communications, 2023)
Abstract The mechanisms by which DNA alleles contribute to disease risk, drug response, and other human phenotypes are highly context-specific, varying across cell types and different conditions. Human induced pluripotent stem cells are uniquely suited to study these context-dependent effects but cell lines from hundreds or thousands of individuals are required. Village cultures, where multiple induced pluripotent stem lines are cultured and differentiated in a single dish, provide an elegant solution for scaling induced pluripotent stem experiments to the necessary sample sizes required for population-scale studies. Here, we show the utility of village models, demonstrating how cells can be assigned to an induced pluripotent stem line using single-cell sequencing and illustrating that the genetic, epigenetic or induced pluripotent stem line-specific effects explain a large percentage of gene expression variation for many genes. We demonstrate that village methods can effectively detect induced pluripotent stem line-specific effects, including sensitive dynamics of cell states.